Efl Students’ Learning Styles Preference And Problems Encountered In Critical Reading Course - Indrayani, Luh; G.A.P. Suprianti; I.K.R. Arthana; N.L.P.S. Paramitha (Universitas Pendidikan Ganesha, 2024)
Several theories in the world of education state that student learning styles must be known by both teachers and students because learning styles play an important role in the learning process. This study aims to identify the preferred learning styles and problems faced by English Language Education students who take the Critical Reading Course. This research is in the form of a descriptive case study with the subject of the study being English Language Education students. Data were collected through questionnaires, observations, and interviews. The data analysis method used is descriptive analysis. The findings of the study show that the most preferred learning style by students is the visual learning style, followed by kinesthetic and auditory learning styles. Some students also prefer multimodal learning styles, such as visual-kinesthetic and visual-auditory. Students with visual-kinesthetic learning styles tend to intertextualize texts to understand the meaning in critical reading texts. The main obstacle students face in reading is lack of focus. Topics that students consider challenging include the main idea implied, supporting details, arguments, and logical fallacies. This study provides valuable information about the learning style of English Language Education students based on the sensory perception dimension. This research suggests that teachers create an inclusive classroom environment by implementing various teaching strategies, media, and activities to accommodate different learning styles of students. In addition, students are expected to be aware of their respective learning styles to acquire material efficiently and enjoyably.